2017
DOI: 10.1098/rsob.160231
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus causes supernumerary foci with centriolar proteins and impaired spindle positioning

Abstract: Zika virus (ZIKV) causes congenital microcephaly. Although ZIKV can impair cell cycle progression and provoke apoptosis, which probably contributes to disease aetiology through depletion of neural progenitor cells, additional cellular mechanisms may be important. Here, we investigated whether ZIKV infection alters centrosome number and spindle positioning, because such defects are thought to be at the root of inherited primary autosomal recessive microcephaly (MCPH). In addition to HeLa cells, in which centros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 47 publications
7
33
0
Order By: Relevance
“…ZIKV infection has been linked to significant defects in centrosome function (54,55). Consistent with these observations, our data reveal ZIKV polypeptide interactions with multiple centrosome and cilia regulatory proteins.…”
Section: Resultssupporting
confidence: 89%
“…ZIKV infection has been linked to significant defects in centrosome function (54,55). Consistent with these observations, our data reveal ZIKV polypeptide interactions with multiple centrosome and cilia regulatory proteins.…”
Section: Resultssupporting
confidence: 89%
“…Most interestingly, NS3 overexpression impaired the structure of centrosome. NS3 may contribute to the centrosome damage induced by ZIKV as reported recently (Gabriel et al, 2017; Wolf et al, 2017). …”
Section: Discussionsupporting
confidence: 59%
“…Subsequently, studies using more recent clinical isolates confirmed similar productive infection and death of NPCs in 2D cultures as well as premature differentiation, aberrant expression of centrosomal proteins, and disrupted centrosomal structure (Gabriel et al 2017). Disruption of the centrosome and spindle positioning was also observed in HeLa cells after ZIKV infection (Wolf et al 2017). Adherens junctions, a connective structure formed among NPCs, appear to be vulnerable to ZIKV infection, which leads to their degradation and reduced mouse NPC proliferation in an NS2A-dependent fashion (Yoon et al 2017).…”
Section: Pathophysiology Of Zikv Infection In the Nervous System Neurmentioning
confidence: 80%